Pelatihan Statistical Package for the Social Sciences (SPSS) Bagi Dosen dan Mahasiswa Untuk Penelitian Kuantitatif - Saftari, Maya; Hengki, Hengki; Sarwindah, Sarwindah; Sinta, Sinta (Journal Of Human And Education (JAHE), 2024)
In the academic world, the ability to perform data analysis is a crucial skill. Both lecturers and students need to master data analysis techniques to support research activities, especially quantitative research. These analysis techniques are supported by proficiency in software that can assist in data processing. A frequently utilized software is SPSS. This SPSS training is designed to enhance the data analysis skills of lecturers and students through face-to-face methods that include presentations, live demonstrations, and interactive practice sessions. The training aims to provide a deep understanding of SPSS usage in various statistical analyses, from data entry to result interpretation. The activity will be conducted in March 2024, with participants being lecturers and students from the Digital Business program. The training evaluation will be carried out comprehensively through direct assessment of participants' abilities to apply SPSS, which includes practical tests. This training is expected to provide maximum benefits to participants, support academic and research activities, and improve the quality of teaching and research outcomes.